Convolution-type integral equation with two kernels and its abstract analog - Poletaev , G. S. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We consider an integral equation of the convolution type with two kernels, generated by functions from some Banach algebras, and a linear equation with two coefficients in abstract rings with factorial pairs of sub-rings. Theorems and formulas have been proved, characterizing the general relation of the solvability problem of the equations with the factorization properties of elements constructed from the kernels and coefficients.